1969
DOI: 10.1007/bf00407105
|View full text |Cite
|
Sign up to set email alerts
|

Studies with deoxyribonucleic acid from blue-green algae

Abstract: DNA from two blue-green algae was isolated and characterized. The buoyant densities, thermal denaturation and re-naturation, thermal melting values, base compositions, sedi-mentation coefficients, and molecular weights were determined. Blue-green algal DNA renatured extensively and at a comparable rate to that of bacterial DNA. The similarities among the kinds of DNA from bacteria and blue-green algae were interpreted to reflect a close relationship. A popular hypothesis to explain the origin of chloroplasts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The data on DNA base composition in Tables 1 to 5 include all values now available for cyanobacteria, derived both from the present study and from preceding publications (Edelman et al, 1967;Craig et al, 1969;Kaye et al, 1967;Stanier et al, 1971;Rippka et al, 1974). A careful comparison of cyanobacterial strain histories (Rippka et al, 1979) has shown that a few of the strains, previously assumed to be of independent origin, are probably identical isolates; in such cases, a value for only one strain is included in the tabulations.…”
Section: Resultsmentioning
confidence: 94%
“…The data on DNA base composition in Tables 1 to 5 include all values now available for cyanobacteria, derived both from the present study and from preceding publications (Edelman et al, 1967;Craig et al, 1969;Kaye et al, 1967;Stanier et al, 1971;Rippka et al, 1974). A careful comparison of cyanobacterial strain histories (Rippka et al, 1979) has shown that a few of the strains, previously assumed to be of independent origin, are probably identical isolates; in such cases, a value for only one strain is included in the tabulations.…”
Section: Resultsmentioning
confidence: 94%
“…Second, because cells of Anabaena sp. have multiple genomic equivalents as calculated from the genetic complexity (3,22) and the amount of DNA per cell (7) and are linked, isolation of recessive mutants requires both segregation of mutant and wild-type forms of the genome and physical disjunction of adjacent cells of a filament bearing the two genomic forms (8). Golden and Wiest (18) first introduced an insertional mutation into the chromosome ofAnabaena sp.…”
mentioning
confidence: 99%
“…For Cyanophyceae see, for instance, Edelman et al (1967), Craig, Leach & Carr (1969), Stanier et al (1971, Stare (1980), and Lachance (1981). Within a genus the GC content does not usually show large differences.…”
mentioning
confidence: 99%